PENGGUNAAN ALIH KODE DAN CAMPUR KODE DALAM ACARA MATANAJWA PADA STASIUN TELEVISI TRANS7 - Sukmana, Ayu Andini; Wardarita, Hj. Ratu; Ardiansyah, Arif (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2021)
This study aims to describe the use of code switching and code mixing in the Matanajwa program on the Trans7 television station. The method used is a qualitative method. The results showed that in the Matanajwa program on Trans7 television station, there was the use of internal code switching and external code switching. The code mixing that occurs is of the type of mixing the code in (inner code mixing) with the level of words, phrases, and reduplication, as well as mixing the code out (outer code mixing) with the level of words, phrases, reduplication, baster, idiom, and clause. Factors causing code switching are speakers and the presence of a third person. Meanwhile, code mixing is caused by the limited use of code switching, the use of popular terms, speakers, speech partners, subject matter (topics), evokes a sense of humor, and is simply prestigious. Then, what was dominant in this event was code mixing. The functions of code switching and code mixing in this event are quoting, accuracy of meaning, expressing emotions, showing self-identity, showing social status/prestige, argumentative, persuasive, and familiarizing.